Modulation of Src Kinase Activity by Selective Substrate Recognition with Pseudopeptidic Cages. Issue 37 (1st June 2021) - Tapia, Lucía; Solozabal, Naiara; Solà, Jordi; Pérez, Yolanda; Miller, W. Todd; Alfonso, Ignacio
Abstract: The selective recognition of tyrosine residues in peptides is an appealing approach to inhibiting their tyrosine kinase (TK)‐mediated phosphorylation. Herein, we describe pseudopeptidic cages that efficiently protect substrates from the action of the Src TK enzyme, precluding the corresponding Tyr phosphorylation. Fluorescence emission titrations show that the most efficient cage inhibitors strongly bind the peptide substrates with a very good correlation between the binding constant and the inhibitory potency. Structural insights and additional control experiments further support the proposed mechanism of selective supramolecular protection of the substrates. Moreover, the approach also works in a completely different kinase‐substrate system. These results illustrate the potential of supramolecular complexes for the efficient and selective modulation of TK signaling. Abstract : How to spare Tyr : The selective recognition of tyrosine residues by pseudopeptidic cages protects the substrates from Src kinase‐promoted phosphorylation. The Tyr kinase‐inhibiting activity of the cages can be satisfactorily explained by the formation of host‐guest complexes. This supramolecular approach represents an appealing alternative to modulating Tyr kinase activity by substrate recognition.